A comparative study on the effects of stress on some aspects of in vitro blood coagulation in two freshwater fish species - Rathete, Sello Athlone (University of Limpopo, 1993)
Refer to the document
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 1993.
Keywords: Stress; Vitro blood coagulation; Freshwater fish species; 597.0929; Blood-Coagulation; Freshwater fishes